Through the funhouse looking glass: Europe's ship of states - Stephan Leibfried; Susan M. Gaines; Lorraine Frisina (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2009)
What is the nature of the European Union? Does it have the characteristics of a state, and if so, which? We employ a single imagea poster that won a Marshall Plan competition in 1950to examine the various legal perspectives of the EU that have emerged over the past six decades. Created as a symbol of European unity at the outset of European integration, the image was used half a century later on the book cover of Andrew Moravcsik's instant classic on intergovernmentalism. Here, we reinterpret the image yet againin four different ways. This attempt to sort out the legal perspectives of the EU was inspired by the Lisbon Treaty Case that is currently before the German Constitutional Court and will be decided in May 2009.
Keywords: 320